2019
DOI: 10.5607/en.2019.28.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Tweety-homolog (Ttyh) Family Encodes the Pore-forming Subunits of the Swelling-dependent Volume-regulated Anion Channel (VRACswell) in the Brain

Abstract: In the brain, a reduction in extracellular osmolality causes water-influx and swelling, which subsequently triggers Cl − - and osmolytes-efflux via volume-regulated anion channel (VRAC). Although LRRC8 family has been recently proposed as the pore-forming VRAC which is activated by low cytoplasmic ionic strength but not by swelling, the molecular identity of the pore-forming swelling-dependent VRAC (VRAC swell ) remains unclear. Here we identify and characterize Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(98 citation statements)
references
References 66 publications
(119 reference statements)
4
88
3
Order By: Relevance
“…Likewise, VRAC has long been proposed to be responsible for the transient volume decrease. We have recently reported that astrocytic TTYH1/2/3 are necessary and sufficient for the regulated volume decrease (RVD) in the hippocampus rather than the transient volume decrease (Han et al 2019). RVD is induced by low-frequency stimulation (1 Hz) for 30 min, which is clearly distinguishable from the transient volume decrease, which is induced by a brief train of high frequency stimulations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, VRAC has long been proposed to be responsible for the transient volume decrease. We have recently reported that astrocytic TTYH1/2/3 are necessary and sufficient for the regulated volume decrease (RVD) in the hippocampus rather than the transient volume decrease (Han et al 2019). RVD is induced by low-frequency stimulation (1 Hz) for 30 min, which is clearly distinguishable from the transient volume decrease, which is induced by a brief train of high frequency stimulations.…”
Section: Discussionmentioning
confidence: 99%
“…We next tested a possible candidate member of the VRAC Tweety-homolog (TTYH) family, which we recently reported to encode the pore-forming subunits of the swelling-dependent volume-regulated anion channel (VRAC swell ) in the brain (Han et al 2019), as a target for transient volume decrease. We injected a mixture of viruses carrying the previously confirmed shRNA for Ttyh1, Ttyh2 and Ttyh3 (Han et al 2019) into hippocampus. We observed no significant difference in IOS baseline change or decay time between Ttyh 1,2,3 triple gene-silenced condition and control shRNA condition (Fig.…”
Section: Volume Transient Is Terminated By CL − Efflux Via Best1mentioning
confidence: 99%
See 1 more Smart Citation
“…It is significant for the appropriate functionality and well-being of the nervous system and is strongly prohibited by a particular cell type called astrocytes, owing to their high and exclusive expression of the water channel, aquaporin-4 [50,51]. Water-influx through AQP4 is initiated by osmolytes that activate an outflow of Cl-and osmolytes by means of some volume-regulated anion channel, and afterwards there is an outflow of water to re-establish the volume [52][53][54][55].…”
Section: Osmolytes As Therapeutic Target Against Neurological Disordersmentioning
confidence: 99%
“…Its levels are associated with osmolytes in the visual but not in the sensorimotor region, indicating the regional specificity of modifications in GABAergic tone in hepatic encephalopathy. Glutamate and other osmolytes are expected to be released through receptors and influence synaptic conduction as well as N-methyl-D-aspartate receptor or metabotropic glutamate receptor-dependent synaptic plasticity [13,55,58]. Alzheimer's disease (AD) is considered a permanent brain disorder that gradually demolishes cognitive functions and ultimately a person's capacity to execute everyday life tasks and behavior.…”
Section: Osmolytes As Therapeutic Target Against Neurological Disordersmentioning
confidence: 99%